Pengaruh Fasilitas Kerja Dan Beban Kerja Terhadap Motivasi Kerja Pegawai - Sri Arita; Fanny Agustin (Jurnal Ecogen, 2022)
Abstract: The goal of this study was to ascertain how the work environment and workload affected the employees of Lima Puluh Kota's Guguak Sub-District Office's motivation to work. Descriptive quantitative research is the method employed, and the sample size is 35 employees from the Guguak District Office in Lima Puluh Kota. Additionally, the entire population is sampled using the saturated sample sampling technique. evaluating the instrument's reliability and validity. Analysis of data with descriptive and inductive methods using the F test and t test for hypothesis testing as well as the normality test, heteroscedasticity test, multicollinearity test, and multiple linear regression. The findings of this study show that (1) work environments and workload have a favorable and significant impact on employee motivation (sig 0.000 0.05). (2) The results show that work amenities have a favorable and substantial impact on employee job motivation (sig 0.004 0.05). (3) The results show that employee work motivation is negatively and significantly impacted by workload (sig 0.002 0.05). Keyword : work facilities , workload , work motivation